The Amateur Astronomer's Guide to the Deep-Sky Catalogs - Cavin, Jerry D. (The Patrick Moore Practical Astronomy Series,, 2012)
All of us familiar with astronomy know of Charles Messier and his early work on creating a catalog of celestial objects. Did you know that Messier was compiling a list of objects to avoid when searching the skies? He was a comet hunter, and he wanted to not mistake other things for comets. Other lists and catalogs followed this, and many, including Messier's, have become popular with amateur astronomers who see it as a challenge to find everything on the list or as a guide on what to see when they look through their telescopes or binoculars. In this "catalog of catalogs," the author introduces the figures behind the most famous of the star catalogs and includes the catalog listings as well. Thus here, all in one book, is your complete guide to the heavenly bodies - including constellations, galaxies, nebulae, supernova remnants, and much more - that most people seek to see when they observe the night sky. Here are enough challenges for a lifetime of exciting viewing!